On the dependence of interfacial resistance on contact materials between cathode and interconnect in solid oxide fuel cells. (3rd June 2021) - Huang, Nan; Han, Beibei; Wang, Yudong; Li, Yuanyuan; Su, Yu; Guan, Wanbing; Zhou, Xiaodong; Chai, Maorong; Singhal, Subhash C.
Abstract: The dependence of interfacial contact resistance (ICR) on contact materials between cathode and interconnect is systematically studied under both isothermal oxidation and thermal cycling conditions. Three kinds of cathode current-collecting layer (CCCL) are used, (La, Sr) (Co, Fe)O3 (LSCF), LSCF+10%Ag, and Ag, and tested in a SUS430/CCCL/SUS430 sandwich structure to simulate the actual operation of the solid oxide fuel cells (SOFCs). Experimental results show that the ICR of LSCF+10%Ag exhibits the smallest value, in comparison with the specimens with LSCF and Ag paste, as well as the sample without a CCCL. For LSCF+10%Ag contact, the ICR increases from 0.0069 mΩ cm 2 to 3.74 mΩ cm 2 under an isothermal condition for 150 h, then increases from 3.74 mΩ cm 2 to 10.79 mΩ cm 2 after 15 thermal cycles. This work provides information for the understanding of possible mechanisms of performance degradation of SOFCs. Highlights: The dependence of ICR on contact materials between cathode and interconnect was systematically studied. Different SUS430/CCCL/SUS430 sandwiches was studied under both isothermal oxidation and thermal cycling conditions. The ICR of LSCF+10%Ag exhibits the smallest value and low degradation rate. The LSCF+10%Ag paste, LSCF cathode and SUS430 interconnects have a good interfacial adhesion.